Chitosan–Starch–Keratin Composites: Improving Thermo-Mechanical and Degradation Properties Through Chemical Modification - Flores‑Hernández, Cynthia G. (2018)
Chitosan–starch polymers are reinforced with different keratin materials obtained from chicken feather. Keratin materials are treated with sodium hydroxide; the modified surfaces are rougher in comparison with untreated surfaces, observed by Scanning Electron Microscopy. The results obtained by Differential Scanning Calorimetry show an increase in the endothermic peak related to water evaporation of the films from 92 °C (matrix) up to 102–114 °C (reinforced composites). Glass transition temperature increases from 126 °C in the polymer matrix up to 170–200 °C for the composites. Additionally, the storage modulus in the composites is enhanced up to 1614% for the composites with modified ground quill, 2522% for composites with modified long fiber and 3206% for the composites with modified short fiber. The lysozyme test shows an improved in the degradability rate, the weight loss of the films at 21 days is reduced from 73% for chitosan-starch matrix up to 16% for the composites with 5 wt% of quill; but all films show a biodegradable character depending on keratin type and chemical modification. The outstanding properties related to the addition of treated keratin materials show that these natural composites are a remarkable alternative to potentiating chitosan–starch films with sustainable features.